Efficacy of entomopathogenic Trichoderma isolates against sugarcane woolly aphid, ceratovacuna lanigera zehntner (Hemiptera: Aphididae) - Md. Shafiqul Islam; Vijay Kumar Subbiah; Shafiquzzaman Siddiquee (MDPI, 2022)
Ceratovacuna lanigera Zehntner (Hemiptera: Aphididae) is a destructive insect pest of sugarcane that is responsible for reducing the quality, yield, and sugar content. Ecofriendly methods of pest control, such as the use of biological control, is encouraged since it does not exhibit the harmful effects that are usually seen when using chemical-based pesticides. Here, we evaluated the efficacy of several entomopathogenic fungi isolates against C. lanigera under laboratory conditions. A total of seven isolates were obtained from agricultural soils that were collected from various locations from Sabah, Malaysia, using the insect bait method. Among the seven, four isolates (TMS114, TMS623, TMS628, and TMS707) were positively identified as T. harzianum (Hypocreales: Hypocreaceae), two isolates (TMS45, TMS321) as T. asperellum (Hypocreales: Hypocreaceae), and one isolate (TMS633) as T. hamatum (Hypocreales: Hypocreaceae) based on a combination of morphological characteristics and molecular data using ITS 1-5.8 S-ITS 2 regions of the rDNA. Four different concentrations (1 × 10⁵, 1 × 10⁶, 1 × 10⁷, and 1 × 10⁸ mL⁻¹) of conidia suspensions of the isolates were applied separately on nymphs and adults of C. lanigera. The results showed that mortality in both nymphs and adults was dependent on the conidia concentration and exposure time. Among the four concentrations, the highest mortality of C. lanigera was found to range from 59.99 to 75.70% for nymphs after 72 h and from 57.45 to 72.31% for adults after 6 days of treatments at the concentration of 1 × 10⁸ conidia mL⁻¹. Trichoderma harzianum (TMS623) showed significantly highest mortality of 75.70% for nymphs and 72.31% for adults among the seven isolates. However, the nymph and adult mortality rates for the isolates were 70.00% & 68.00% for TMS114, 66.42% & 63.10% for TMS628, 67.85% & 65.24% for TMS707, 61.42% & 58.80% for TMS45, 59.99% & 57.45% for TMS321 and 63.56% & 60.91% for TMS633, respectively. For nymph mortality, T. harzianum (TMS623) showed a LC₅₀ (lethal concentration) value of 6.30 × 10⁵ conidia mL⁻¹ and LC90 value of 3.01 × 109 conidia mL⁻¹, respectively, and for adult mortality, the values were found of 6.16 × 10⁵ conidia mL⁻¹ for LC₅₀ and 2.23 × 1010 conidia mL⁻¹ for LC₉₀, respectively. The lethal time (LT) values for nymph and adult mortality were found of 42.65 h and 3.89 days for LT50 and 93.32 h and 8.70 days for LT90 by T. harzianum (TMS623). Therefore, T. harzianum (TMS623) showed more pathogenic potential against C. lanigera and can be further applied to determine its efficacy under field conditions. To our best knowledge, this is the first report of T. harzianum, T. hamatum, and T. asperellum species that are used as entomopathogenic fungi against sugarcane woolly aphid, C. lanigera.